2016
DOI: 10.1038/srep22293
|View full text |Cite
|
Sign up to set email alerts
|

A physiologically based kinetic model for elucidating the in vivo distribution of administered mesenchymal stem cells

Abstract: Although mesenchymal stem cells (MSCs) present a promising tool in cell therapy for the treatment of various diseases, the in vivo distribution of administered MSCs has still been poorly understood, which hampers the precise prediction and evaluation of their therapeutic efficacy. Here, we developed the first model to characterize the physiological kinetics of administered MSCs based on direct visualization of cell spatiotemporal disposition by intravital microscopy and assessment of cell quantity using flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 36 publications
(63 reference statements)
0
38
0
Order By: Relevance
“…Notably, this analysis allowed to calculate changes in MSC distribution occurring in disease states entailing loss of function of specific organs ( e.g ., heart failure). In line with other studies, supply through the hepatic artery was then suggested as an alternative route of administration to avoid lung overload[23,33]. …”
Section: Pharmacokinetics Aspects - Biodistributionmentioning
confidence: 66%
See 2 more Smart Citations
“…Notably, this analysis allowed to calculate changes in MSC distribution occurring in disease states entailing loss of function of specific organs ( e.g ., heart failure). In line with other studies, supply through the hepatic artery was then suggested as an alternative route of administration to avoid lung overload[23,33]. …”
Section: Pharmacokinetics Aspects - Biodistributionmentioning
confidence: 66%
“…This phenomenon could explain the extremely high percentage of MSCs localized in the lung after intravenous injection[18,26,29]. Recently, mouse models have confirmed the pulmonary localization of MSCs[30-33]. Furthermore, infusion of MSCs led to pulmonary parenchymal edema and hemorrhage at the highest dose tested[34].…”
Section: Pharmacokinetics Aspects - Biodistributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, modeling has been used to examine of the network motifs or the parameter sets able to generate oscillations 15,16 or spatial patterns 17 , or the noise characteristics of signaling networks [18][19][20][21] . They may also serve as the foundation for practical applications, such as designing treatments of diseases [22][23][24] and interpreting the pharmacokinetics of drugs [25][26][27] . Many mechanism-based models cannot be solved analytically and have to be analyzed by numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) is one of the most promising and widely used therapeutic cells for many debilitating diseases including liver cirrhosis, diabetes, spinal cord injury and myocardial infarction. Recently, a whole body PBPK model has been developed based on the organ disposition and cell-tissue interactions of GFP-expressing MSCs visualised by MPM [72]. This imaging technique opens up a new window for more in-depth investigation about the disposition of molecules, nanoparticles and biological agents in the liver and other organs to understand their in vivo pharmacokinetics and pharmacodynamics.…”
Section: Therapeutic Cell Imagingmentioning
confidence: 99%